SCIENCE-TECHNOLOGY ANALYSIS ON THE USE OF GENTA UTER IN HINDU RELIGIOUS RITUALS - Krisna S. Yogiswari; I Kadek Arya Sugianta (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2022)
This article traces the correlation of Genta Uter in yadnya ceremonies using a science-technology perspective. The news of Genta Uter or singing bowl through the phenomenon of the 'rain handler' of Moto GP Mandalika made Genta Uter increasingly popular, not only among the Hindu community. Genta Uter, as one of the means of ceremonies, has been carried out for a long time and has become a mandatory and traditional standard. The use of Genta Uter certainly has a variety of religious meanings in addition to being a legacy of tradition, which can positively impact the environment. Using the Matlab application, they discovered a rational justification for using Genta Uter as a tool for Hindu yadnya ceremonies through a quantitative descriptive approach with experimental test methods based on Fast Fourier Transform (FFT). Genta Uter's voice is positioned as a positive voice with positive energy that can be compared to Western Classical Music such as Mozart and Beethoven, thanks to the acquisition of Genta Uter's sound in various sizes and durations. The Genta Uter sound, which has the qualities of a joyous sound and positive energy, makes it a sound that can promote calm and relaxation, which can promote health in living things so that it can spread positive vibrations throughout the surrounding area.